2022
DOI: 10.3390/en15051637
|View full text |Cite
|
Sign up to set email alerts
|

Customer Perceived Risk Measurement with NLP Method in Electric Vehicles Consumption Market: Empirical Study from China

Abstract: In recent years, as people’s awareness of energy conservation, environmental protection, and sustainable development has increased, discussions related to electric vehicles (EVs) have aroused public debate on social media. At some point, most consumers face the possible risks of EVs—a critical psychological perception that invariably affects sales of EVs in the consumption market. This paper chooses to deconstruct customers’ perceived risk from third-party comment data in social media, which has better coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Delays, changes of mind or cancelations by consumers are related to the influence of perceived risks (Dou et al. , 2021; Shu et al. , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays, changes of mind or cancelations by consumers are related to the influence of perceived risks (Dou et al. , 2021; Shu et al. , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Perceived risk is consumers' expectation of negative utility when purchasing a particular product/service. Delays, changes of mind or cancelations by consumers are related to the influence of perceived risks (Dou et al, 2021;Shu et al, 2022). Perceived risk negatively affects consumers' attitudes and intentions to buy innovative products/services via omnichannel (Huang et al, 2014;Shu et al, 2022).…”
Section: Antecedents Decisions and Outcomesmentioning
confidence: 99%
“…Third, it is suggested to provide convenient services for customers. Despite the rapid acceptance in China's NEVs market, Chinese consumers still have various perceived risks with negative emotions, particularly time risks [19]. Time problems are the most likely to give users a bad experience.…”
Section: Using the 4cs Marketing Model To Improve Customer Experiencementioning
confidence: 99%
“…The fourth is to communicate with customers. Among the consumers' considerations when buying NEVs, social connection is one of the most important factors [19]. This requires brands to strengthen interaction with consumers in order to understand their needs.…”
Section: Using the 4cs Marketing Model To Improve Customer Experiencementioning
confidence: 99%
“…Bennett et al [19] measured the legal risk by counting the number of litigious words in Form 10-Ks and found that the legal risk has negative effects on S&P credit ratings. Shu et al [20] deconstructed the customer-perceived risk from comment data in social media and provided a new tool for the multi-dimensional capture of risk. However, other than the risk information, more information included in Form 10-Ks, such as the business, history, and staff comment section of companies, would disturb the risk measurement.…”
Section: Introductionmentioning
confidence: 99%